Punicalagin's Protective Effects on Parkinson's Progression in Socially Isolated and Socialized Rats: Insights into Multifaceted Pathway - Hoda A. Salem; Karema Abu-Elfotuh; Sharifa Alzahrani; Nermin I. Rizk; Howaida S. Ali; Nehal Elsherbiny; Alhanouf Aljohani; Ahmed M. E. Hamdan; Panneerselvam Chellasamy; Nada S. Abdou; Ayah M. H. Gowifel; Alshaymaa Darwish; et al. (MDPI AG, 2023)
Parkinson's disease (PD) is a gradual deterioration of dopaminergic neurons, leading to motor impairments. Social isolation (SI), a recognized stressor, has recently gained attention as a potential influencing factor in the progress of neurodegenerative illnesses. We aimed to investigate the intricate relationship between SI and PD progression, both independently and in the presence of manganese chloride (MnCl2), while evaluating the punicalagin (PUN) therapeutic effects, a natural compound established for its cytoprotective, anti-inflammatory, and anti-apoptotic activities. In this five-week experiment, seven groups of male albino rats were organized: G1 (normal control), G2 (SI), G3 (MnCl2), G4 (SI + MnCl2), G5 (SI + PUN), G6 (MnCl2 + PUN), and G7 (SI + PUN + MnCl2). The results revealed significant changes in behavior, biochemistry, and histopathology in rats exposed to SI and/or MnCl2, with the most pronounced effects detected in the SI rats concurrently exposed to MnCl2. These effects were associated with augmented oxidative stress biomarkers and reduced antioxidant activity of the Nrf2/HO-1 pathway. Additionally, inflammatory pathways (HMGB1/RAGE/TLR4/NF-ᴋB/NLRP3/Caspase-1 and JAK-2/STAT-3) were upregulated, while dysregulation of signaling pathways (PI3K/AKT/GSK-3β/CREB), sustained endoplasmic reticulum stress by activation PERK/CHOP/Bcl-2, and impaired autophagy (AMPK/SIRT-1/Beclin-1 axis) were observed. Apoptosis induction and a decrease in monoamine levels were also noted. Remarkably, treatment with PUN effectively alleviated behaviour, histopathological changes, and biochemical alterations induced by SI and/or MnCl2. These findings emphasize the role of SI in PD progress and propose PUN as a potential therapeutic intervention to mitigate PD. PUN's mechanisms of action involve modulation of pathways such as HMGB1/RAGE/TLR4/NF-ᴋB/NLRP3/Caspase-1, JAK-2/STAT-3, PI3K/AKT/GSK-3β/CREB, AMPK/SIRT-1, Nrf2/HO-1, and PERK/CHOP/Bcl-2.